Civil service reform in the People's Republic of China - Maharay, George
The people's Republic of China has launched an ambitious effort to establish a comprehensive civil service system with the help of various groups. Author discusses the major steps necessary to install a new personnel system which omc;ides : (1) Establishing the conceptual frame work for the system;(2) Creating the organisational framework necessary to carry out the program; (3) Developing and testing regulations amd [rpcedires fpr tje mew suste,; (4) Implementating the programme in all the agencies and organisatiions covered by it and (5) Evaluationg results and making revisions, as necessary.
Keywords: Economic Reforms; Civil Service - China